Reflections on Slovenian Rural Geography: Development, Dilemmas, and Overlooked Topics - Kumer, Peter (Podeželje, 2026)
The paper discusses the development of rural geography in Slovenia and its interrelation with spatial, demographic, and socio-cultural dimensions. The theoretical part presents various definitions of the rural areas and the evolution of its understanding over time. The analysis of Slovenian research shows that attention has long been focused mainly on processes of urbanization, suburbanization, and rural depopulation, while social dimensions were often overlooked. In recent years, however, an increasing number of studies have addressed vulnerable groups such as the elderly, farm women, the Roma population, and queer communities, indicating a shift towards a more inclusive understanding of rural space. The paper highlights the need for a holistic and interdisciplinary approach to the study of rural areas.